Ultrasound-guided percutaneous microwave ablation of parotid gland adenolymphoma: A case report. Issue 35 (August 2019) - Jin, Mingyue; Fu, Jili; Lu, Jianbo; Xu, Wanying; Chi, Hui; Wang, Xue; Cong, Zhibin
Abstract: Rationale: Parotid gland adenolymphoma is one of the most common benign tumors in parotid gland, and mainly treated by surgery. Despite the widespread of ultrasound-guided percutaneous microwave ablation, there is no report concerning its application in parotid gland adenolymphoma. Herein, we reported a 2-year follow-up result of a male patient underwent ultrasound-guided percutaneous microwave ablation for parotid gland adenolymphoma. Patient concerns: A 73-year-old man was admitted due to a hypoechoic nodule measuring 2.67 × 1.42 × 1.35 cm in posterior-inferior area of parotid gland with a high flow velocity in color Doppler flow imaging. Diagnose: The lesion was pathologically diagnosed as parotid gland adenolymphoma. Interventions: Ultrasound-guided percutaneous microwave ablation was performed to the tumor due to the fact that the patient refused to receive an open surgery in consideration of older age. Outcomes: The ablation procedure lasted about 2 minutes and 15 seconds, without significant adverse effect. The reduction ratios of tumor at postoperative 1 and 3-month were 53% and 82%, respectively. The tumor was fully absent at postoperative 8-month evaluation. Finally, there was no evident recurrence at postoperative 24-month evaluation. Lessons: Ultrasound-guided percutaneous microwave ablation is a safe and effective treatment for parotid gland adenolymphoma, which may serve as a novel alternative approach for patients unsuitable for open surgery.